Pembelajaran Berbasis Permainan Tradisional untuk Mengembangkan Fisik Motorik Anak Usia Dini - Andri Santoso; Najamuddin Najamuddin; Sofa Tiatahulhusna; Nurul Hayati; Kholisatul Husna Mizati; Zurriyatun Sholihah (Indonesian Journal of Innovation in Education Research, 2026)
Children have a strong connection with various forms of play. In daily life, both traditional and modern games are always part of their activities. Play is considered essential because it serves as a medium to support physical and motor development in Early Childhood. Today, the modern games favored by children in urban areas tend to stimulate cognitive abilities more than motor skills. Therefore, parents living in urban settings are encouraged to introduce games that can strengthen children's muscle development, one of which is through traditional games. Unfortunately, traditional games are increasingly marginalized because they are viewed as outdated and physically demanding. In fact, when examined more closely, various types of traditional games offer numerous benefits, including: (1) developing healthy, fit, strong, and competitive physical abilities; (2) fostering mental aspects such as sportsmanship, tolerance, discipline, and democratic attitudes; (3) building moral character that is sensitive, honest, and sincere; and (4) enhancing social abilities such as competitiveness, cooperation, discipline, friendliness, and national awareness.